A study of effective one-on-one play during set-defense in handball - Funaki, H.; Aida, H. (Japan Journal of Physical Education, Health and Sport Sciences, 2014)
The purpose of this study was to examine the effectiveness of one-on-one play during set-defense in handball, and to gain practical data for development of effective training methods. A total of 447 one-on-one plays were compared with regard to success or failure in blocking the breakthrough at three levels: world class, Japanese elite, and Japanese college level. The one-on-one play was divided in three phases: the first was that when the passer possessed the ball, the second was that when the ball was in the air, and the third was that when the player marked by a defense player possessed the ball. The interactions between plays in each phase and success or failure in blocking the breakthrough were analyzed at each level. The main results were as follows. 1) Effective one-on-one play was when the defense player aggressively blocked the player with the ball and moved forward with physical contact. 2) At the Japanese level it was important to define the guidelines for one-on-one play while the player had the ball, in order to increase the success rate of blocking the breakthrough during one-on-one play. 3) At Japanese elite level, effective one-on-one play could not be established while the player marked by a defense player did not possess the ball. 4) At Japanese college level, defenders selected one-on-one play around the ball while the player marked by the defense player did not possess the ball, and one-on-one defence failed. For consistent coaching in Japan, it was important to adopt one-on-one play around the marking player while the player marked by a defense player did not possess the ball, in order to increase the success rate of blocking the breakthrough during one-on-one play.